Analysis of Education Management in Singapore - Siti Nurhasanah; Fenti Sanda; Nuri Lathifa Brilianti; Yusuf (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Education management is a process of planning, organizing, implementing and evaluating by using existing resources to achieve predetermined goals related to education. The aim of this research is to find out how education units are managed in Singapore, from which we can draw inspiration and important lessons to improve the education system in our country. This research uses the literature study method or literature study. Literature studies can be obtained from various sources, including journals, books, documentation, the internet and libraries. The data used in this research comes from the results of research that has been carried out and published in national and international online journals. Literature study was used to collect information about the management of the education system in Singapore. Next, the collected data will be analyzed systematically to identify relevant research findings and produce appropriate recommendations. The results of the discussion show that Singapore has proven success in having a superior, quality education system and encouraging strong economic growth.